Massacre at the Champ de Mars : popular dissent and political culture in the French Revolution - Andress, David, 1969- (Royal Historical Society studies in history. New series., 2000)
On 17 July 1791 the revolutionary National Guard of Paris opened fire on a crowd of protesters: citizens believing themselves patriots trying to save France from the reinstatement of a traitor king. To the National Guard and their political superiors the protesters were the dregs of the people, brigands paid by counter-revolutionary aristocrats. Politicians and journalists declared the National Guard the patriots, and their action a heroic defence of the fledgling Constitution.